The Professional Competencies of Foreign Language Teachers from the view of Administrators and Teachers in Basic Teaching Schools - A Field Study in Lattakia City - Zreiki, Hyam (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The Research aims to investigate the administrators and teachers opinion in the degree of having of Professional Competencies of Foreign Language Teachers of the Basic Teaching Schools in Lattakia City, and to study the different of such opinions according to variables (sex, expertness, the functional name). To achieve the objectives of the research, a questionnaire composed was designed including (70) items included Professional Competencies; distributed to the four areas (Language, teaching, Class Management, evaluation). then applied to a sample of (222) managers and teachers for the academic year 2017/2018. The present research used the descriptive analytical approach. Validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Tishreen university. Pilot sample consisted of (42) teachers, Reliability was established by Cronbach – Alpha Reliability at lest (0.921). The final results showed that possession the Professional Competencies of Foreign Language Teachers were middle rated, the results did show statistical significance differences among sample answers averages in Professional Competencies of Foreign Language Teachers according to the variables of expertness in favor of more than 10 years, also to the variable the functional name in favor of teachers. As a result of the research conducted, the main recommendations are to create a cognitively enriched environment for English language teachers by conducting professional development workshops.